The existing situation and challenges facing acceptance and care of children in substitute families - H Sepehr (JRI, 2001)
In different cultures across the world, families without or wishing to have more children proceed to adopt or foster them from other families or from children who have no known families. Adoption and foster care have been considered as effective means of confronting negative effects of infertility. Adoption and foster care have positive roles in giving the children the right guidance and help the progress of de-institutionalization and making the proper growth condition for children in family. Major kinds of child training in most countries and in Iran are adoption and foster care. After revolution, responsibilities related to adoption have been given to social welfare organization and by prohibition of adoption by foreign nationals, Iranian families had a better chance for child adoption. Answering to the needs of applicant families and children during different stages of decision-making, adoption and child train, need scientific programming, development of legal and executive structures. More familiarity with characteristics and existing challenges of child adoption, prepare programming for change and improvement of the present situation. Reviewing the present situation and using the local and international experience of government monitor and control, improving standards of services, close correlation between infertility treatment centers and child adoption centers and developing consultation services to families before and after adoption are some steps which seem necessary. Specialization in consultation delivery and caring about basic belief are other necessary aspects in proper programming.
Keywords: Infertility, Child adoption, Foster care